Loading...

It equals 6

It equals 7

-2

22 = 4

I come up with 20.

The sum of 2 plus 0 plus 0 plus 0 plus 0 plus 0 plus 0 plus 0 plus 0 plus 0 plus 0 plus 0 plus 0 plus 0 plus 0 plus 0 equals 2.

0+2

-2

(-1, 0)

x3 + 343 = 0 (x + 7)(x2 - 7x + 49) = 0 So x = -7 or x = [7 +/- sqrt(-147)]/2 The latter two roots are [7 +/- 7i*sqrt(3)]/2 or 7/2*[1 +/- i*sqrt(3)]

0

y = 0x = y + 2plug 0 in for yx = 0 + 2x = 2

2 plus 0 equals 2 because if you add 0,the other number will be the same.Their is also another way to write 2 plus zero.In numbers,it goes like this.2+0=2.

(0, ), (2, ), ( , 0) 4 2 4

3x + 2 = 0 3x = -2 x = -2/3

7x + 2 = 6x + 2 if and only x = 0.

So 4x + 2 = 2. x = 0

-2

(0, 2)

because when you add 1 to 0 it is 2

100101 1 times 2^0 = 1 PLUS 0 times 2^1 = 0 PLUS 1 times 2^2 = 4 PLUS 0 times 2^3 = 0 PLUS 0 times 2^4 = 0 PLUS 1 times 2^5 = 32 EQUALS 37

x2-x3+2x = 0 x(-x2+x+2) = 0 x(-x+2)(x+1) = 0 Points of intersection are: (0, 2), (2,10) and (-1, 1)

x^2 + 3x + 7 = 6x + 18 x^2 - 3x - 11 = 0

2x^2 + 8x + 3 = 0

1 + 1 = 2 1 = 2 - 1 1 + 1 - 2 = 0 0 = 2 - 1 - 1